Dysregulation of Lipid Metabolism in Aging Meibomian Glands and Its Molecular Markers - Butovich, Igor A.; Wilkerson, Amber; Yuksel, Seher (International journal of molecular sciences, 2023)
The main function of exocrine Meibomian glands (MGs) is to produce a lipid-rich secretion called meibum which plays a critical role in maintaining the ocular surface homeostasis of humans and most mammals. The chemical composition of meibum, and its quantity produced by MGs, largely determine whether it can fulfill its role successfully. Aging was frequently associated with the onset of various MG-related pathologies. The goal of this study was to determine how aging affects the chemical composition and quantity of meibum in mice, and identify possible molecular markers of aging. Unbiased, untargeted and targeted lipidomic evaluation of mouse MG lipids was conducted using liquid chromatography—high-resolution mass spectrometry, and the results were analyzed using Principal Component, Orthogonal Projections to Latent Structures Discriminant, and Partial Least Square Discriminant Analyses. We found that aging leads to dysregulation of lipid metabolism in MGs, changing the ratios of major classes of MG lipids (such as wax esters, triacylglycerols, and phospholipids) in a progressive manner. Several lipid species that belong to these groups of MG lipids are proposed as clear markers of aging in a mouse model.